2019
DOI: 10.1007/s13312-019-1665-5
|View full text |Cite
|
Sign up to set email alerts
|

Linear Verrucous Epidermal Nevus

Abstract: An 11-year-old previously healthy girl presented with an acute eruption in inguinal folds. Examination revealed a 3 cm erythematous and annular patch with peripheral collarette scaling and fine wrinkling in the center, associated with similar but smaller lesions, limited to the groins (Fig. 1). The rest of the physical examination, including mucous membranes and skin folds was within normal limits. Mycologic evaluation ruled out dermatophytosis. The diagnosis of pityriasis rosea was made based on the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Differential diagnoses of LVEN also include linear planus, psoriasis, lichen striatus and porokeratosis. 8 In our case, biopsy of the lesion was not considered as the diagnosis of Tuberous sclerosis was certain. 5 A case described by Elam et al 9 showed similar white epidermal nevus in a neonate on day 1 of life but these appeared as plaques and papules that later on was diagnosed as TSC.…”
Section: Discussionmentioning
confidence: 80%
“…Differential diagnoses of LVEN also include linear planus, psoriasis, lichen striatus and porokeratosis. 8 In our case, biopsy of the lesion was not considered as the diagnosis of Tuberous sclerosis was certain. 5 A case described by Elam et al 9 showed similar white epidermal nevus in a neonate on day 1 of life but these appeared as plaques and papules that later on was diagnosed as TSC.…”
Section: Discussionmentioning
confidence: 80%